THE APPLICATION OF BANKRUPTCY PREDICTION ANALYSIS USING ALTMAN Z-SCORE AND SPRINGATE METHODS AT PT. GUDANG GARAM TBK - Robot, Selmy (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
Globalization era, business is something that is familiar and contributes to the economy of a country. The business world continues to develop in accordance to the demands of changing times. Given these developments, a company is required to be able to adapt in order to maintain the viability of the company. Companies must be able to survive in the fierce competition and outperform competing products, especially in dealing with the crises that occur. The objective of this research is: To find out what are the results of the analysis in PT. Gudang Garam Tbk period 2008 - 2012 using method of Altman Z-Score and Springate. Theory supporting research is bankruptcy prediction. Population is manufacturing company engaged in the industrial sector of the consumer goods with sub-sector of cigarettes and listing on the Indonesian Stock Exchange with sample of financial report from 2008 until 2012. Results and conclusions are bankruptcy analysis using the Altman Z-score model of PT. Gudang Garam Tbk. for the period 2008-2011 is in a position of the healthy company. While in 2012 the company touched the position of grey area and the Springate models classified the company not potentially bankrupt. Based on the analysis results by using the Altman Z-score and Springate models, it can be seen that the liquidity and inefficient management extremely affect to financial performance of the company. Keyword: bankruptcy prediction, altman z-score, springate